FORMULATION OF CRIMINAL LAW POLICY REGARDING NIHIL VERDICTS IN INDONESIAN CRIMINAL COURTS - Hensi Septia Utami; Nurini Aprilianda; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
The verdict of acquittal in the application of law enforcement still has problems, namely the existence of a conflict of norms or a regulatory gap, whereby Article 193 of the Criminal Procedure Code